Validity of leukocyte esterase reagent (LER) strip in diagnosing infectious pleural effusion - Kalaisezhian, N.; Irsath, S.; Shankar, R. (International Journal of Advances in Medicine, 2018)
Background: Pleural fluid sampling and analysis are essential to confirm an infection. In a resource-limited health care setting or if biochemistries of the aspirated fluid are not available on an emergency basis, urine reagent strips applied to pleural fluid may expedite diagnostic information. Present study was aimed to evaluate the effectiveness of leukocyte esterase reagent (LER) strip in diagnosing infectious pleural effusion and to correlate the reaction of LER strip with various stages of infectious effusions. Methods: A prospective longitudinal study was conducted in the medical ward of Government Mohan Kumaramangalam Medical College Hospital for a period of one year. Pleural effusion patients with associated immuno-compromised conditions like diabetes mellitus, patients on steroids, HIV reactive patients, chronic obstructive lung disease were included for the study. A totalof 84 patients were included for the study. Exploratory thoracocentesis was done with an 8 mm needle and pleural fluid was obtained and sent for cell count and biochemical testing. The pleural fluid was also tested using the leukocyte esterase reagent strip. The results were recorded as 0, 1+, 2+, 3+ based on the density of violet colour. Results: The leukocyte esterase reagent strip test showed totally negative results in all patients with transudative pleural effusion and also in patients with tuberculous pleural effusion, whereas among patients with infectious pleural effusion other than tuberculosis LER strip test showed negative to only 15% of the patients and for remaining it ranged from 1+ to 3+. The validity of leukocyte esterase strip test was tested in comparison with the gold standard culture test. The accuracy of LER strip test was found to be 88.6%, and the sensitivity and specificity was 90.2% and 66.2% respectively. Conclusions: Reagent strips may speed up the bedside diagnosis of infectious effusions. However, where access to standard biochemical pleural fluid analysis is not available this dipstick tests would add value to the management of the patients.